Relationships between personality traits, negative affectivity and procrastination in high school students - Randjelović, Dušan; Vujičić, Milena; Nikolić, Gordana (Vojnosanitetski pregled, 2021)
Introduction/Aim. Procrastination includes intentional postponing of either starting or finalizing a task and is one of the most important aspects of an academic achievement. The aim of this study was to examine the possibility of procrastination prediction based on the values of certain personality traits and negative affective states (anxiety, depression, stress) in high school students. Methods. The research was conducted over a sample of 900 high school students from 9 high schools in Niš attending the 3rd and 4th grade. The research included the following instruments: The Big Five Inventory (BIF), Depression, Anxiety and Stress Scale (DASS-21), as well as the Procrastination Scale. Results. The model consisting of personality traits was a statistically meaningful predictor of procrastination. Prediction variables found to be statistically significant were neuroticism, as a positive correlate of procrastination, and conscientiousness, as a negative correlate. None of the negative affectivity dimensions (anxiety, depressiveness and stress) was partially shown to be a significant predictor. Conclusion. The lack of conscientiousness can be considered to be the core of procrastination, whereas neuroticism, i.e. some of its facets, such as anxiety, may be encouragement to avoid a task. Obtained results may be used as suggestions to psychological institutions in schools as to which factors are significant for perceiving procrastination problems with students.
Keywords: anxiety; personality assessment; procrastination; students; surveys and questionnaires